Isolation of endophyte microorganism of Acacia mangium - Abdul Latif, Julia (2019)
Recent years Acacia mangium plantations were attacked by serious wilt disease and cause the destruction of the plantation. Owner of the plantation should take this matter seriously and find the best treatment to overcome this wilt disease. This study was conducted to find a biological control especially endophyte microorganisms to overcome the pathogen of wilt disease. To perform this study, healthy seedling of Acacia mangium and its gummosis were collected randomly at Sultan Idris Shah Forest Education Centre and brought to the Plant Pathology Laboratory, Faculty of Forestry. The fresh sample was then cultured into Potato Dextrose Agar (PDA). After a few days of incubation, a microorganism that was grown on PDA were subcultured into special media respectively. In total 76 microorganisms that have been isolated were shortlisted and categorized into fungi and bacteria with similar morphology. This consist of 12 fungi isolates and 11 bacteria isolates. To test their capability, the antagonistic test was done between isolated endophyte microorganisms against Ceratocystis fimbriata and several selected pathogen. This test was performed by the dual culture method. From this activity, all the 12 fungi showed positive inhibition against Ceratocystis fungus. The fungus that showed the highest inhibition is the fungus isolated from gummosis which is D(4) fungus with 64.58% inhibition. The lowest inhibition was the fungus isolated from root nodule which is HS/N3(C)1 fungus which is 12.50% inhibition. Meanwhile, for endophyte bacteria, only 2 from 11 bacteria showed positive inhibition against Ceratocystis fungus. The bacteria were HS/R2(A)2 isolated from primary root and have 8.33% inhibition and HS/N2(A)1 is isolated from root nodule with 2.08% inhibition.